ONLINE PURCHASING DECISION AMONG MUSLIM UNIVERSITY STUDENTS IN MALAYSIA - Wan Noor Hazlina Wan Jusoh; Nur Syaqirah Binti Mohd Razali (Journal of Islamic, Social, Economics and Development, 2022)
The growth of internet technology has found a strong impact on global business. The internet created a new environment of e-commerce and has provided opportunities to connect people through the internet worldwide. According to the study, internet usage and online shopping are most common in the university age 18-30 years old students even though they do not have sufficient funds for shopping but the university students found on the top list are using the internet and have great intentions towards online shopping. This research aim is to study the online purchasing decision among Muslim university students in Malaysia. A standard survey questionnaire was used as the primary data collection method then distributed to Muslim students of Malaysian universities through links via social media. The data of the online purchasing decision factors were analyzed. It was found that most of the respondents were positive with the questions asked. Thus, it is suggested the improvement of e-security on online websites to increase the safety of Muslim university students in Malaysia